Leukocytosis of Unknown Origin: Gangrenous Cholecystitis - Amara Jyothi Nidimusili; M. Chadi Alraies; Naseem Eisa; Abdul Hamid Alraiyes; Khaldoon Shaheen (Case Reports in Medicine)
There have been case reports where patients admitted with acute cholecystitis, who were managed conservatively, had subsequently developed GC (gangrenous cholecystitis). The current case is unique, since our patient denied any prior episodes of abdominal pain and the only tip off was leukocytosis. A high index of suspicion is essential for the early diagnosis and treatment of GC. GC has a mortality rate of up to 22% and a complication rate of 16–25%. Complications associated with GC include perforation, which has been reported to occur in as many as 10% of cases of acute cholecystitis. The radiological investigations may not be conclusive. Ultrasonography usually serves as the first-line imaging modality for the evaluation of patients with clinically suspected acute cholecystitis. However, CT can play an important role in the evaluation of these patients if sonography is inconclusive. There is a need for an early (if not urgent) surgical intervention in acute cholecystitis (whether laparoscopic or open surgery) in order to decrease the time elapsed from the start of symptoms to admission and treatment.